2014
DOI: 10.1016/j.csbj.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic clusters of transcription factor binding sites: A model system for understanding the physical mechanics of gene expression

Abstract: The organization of binding sites in cis-regulatory elements (CREs) can influence gene expression through a combination of physical mechanisms, ranging from direct interactions between TF molecules to DNA looping and transient chromatin interactions. The study of simple and common building blocks in promoters and other CREs allows us to dissect how all of these mechanisms work together. Many adjacent TF binding sites for the same TF species form homotypic clusters, and these CRE architecture building blocks se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 75 publications
2
52
0
Order By: Relevance
“…These dependencies, which we found for the vast majority of TFs, are consistent with early genomic observations showing that TATA-box-containing promoters are generally AT rich, while TATA-less promoters have a high GC content (Sandelin et al 2007;Yang et al 2007). It was previously suggested that the homotypic clusters are important components of the regulatory elements and might have a functional advantage in facilitating the recruitment of TFs (Lifanov et al 2003;Sinha et al 2008;Gotea et al 2010;Ezer et al 2014;Crocker et al 2015). We conducted a systematic, TF binding site-based examination, measuring the prevalence of homotypic clusters for 21 and 56 TFs from different families, employing both in vitro and in vivo data sets, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These dependencies, which we found for the vast majority of TFs, are consistent with early genomic observations showing that TATA-box-containing promoters are generally AT rich, while TATA-less promoters have a high GC content (Sandelin et al 2007;Yang et al 2007). It was previously suggested that the homotypic clusters are important components of the regulatory elements and might have a functional advantage in facilitating the recruitment of TFs (Lifanov et al 2003;Sinha et al 2008;Gotea et al 2010;Ezer et al 2014;Crocker et al 2015). We conducted a systematic, TF binding site-based examination, measuring the prevalence of homotypic clusters for 21 and 56 TFs from different families, employing both in vitro and in vivo data sets, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…As shown, SP1 (a C2H2 protein) and ELF1 (an ETS protein), which bind GC-rich motifs, have a clear preference for high GC environments, while HOXA2 (a homeodomain protein), which binds an AT-rich motif, is surrounded by an AT-rich region. This correlation could be related to the presence of multiple low-affinity binding sites of the same TF (homotypic clusters), which have been shown to be enriched in promoters and enhancers (Lifanov et al 2003;Sinha et al 2008;Gertz et al 2009;Gotea et al 2010;Ezer et al 2014;Crocker et al 2015). We therefore sought to systematically examine the prevalence of homotypic clusters in our data sets.…”
Section: Tf Binding Sites Are Preferentially Found In Homotypic Envirmentioning
confidence: 99%
“…4B, figs. S22A, S23–S25) (18, 19). Humans, chimpanzees, gorillas, orangutans, and baboons, which all have CM connections (2), all possess these FEZF2 binding sites in their putative PlexA1 cis -regulatory elements (Fig.…”
mentioning
confidence: 99%
“…Other computations found homotypic clusters in human and other vertebrate genomes for all five significant clusters whose spreads exceeded 10 bp [32, 33]. Experiments also support the biological importance of SP1 homotypic clusters [34].…”
Section: Resultsmentioning
confidence: 64%